Intercambios epistolares entre Córdoba, Buenos Aires y Roma: circulación de imágenes, objetos devocionales y documentos eclesiásticos durante el período de supresión jesuita - Vanina Scocchera (Centre de Recherches sur les Mondes Américains, 2017)
During the suppression and restoration of the Society of Jesus, the expelled Jesuits developed heterogeneous actions in order to promote their restoration and reinforce their identity. Meanwhile, Priest Gaspar Juárez – exiled in Italy – promoted Jesuits cults and their persistence on both sides of the Atlantic. Through private networks, Priest Juárez encouraged the circulation of ideas, images, devotional objects, books and pontifical documents. These goods proved to be effective so as to reach the priest’s goals in Córdoba, Buenos Aires and Rome.From an epistolary exchange among Priest Juárez in Rome, his benefactor Ambrosio Funes in Córdoba, and Blessed María Antonia de la Paz y Figueroa – follower of Ignatian Exercises in Buenos Aires –, we intend to analyse the ways in which images and devotional objects were exchanged and valued in strategies prone to promote Society of Jesus’s cults and practices in local spheres during its suppression. Likewise, we will analyse ways by which images and devotional objects were resignified according to the obtaining of personal benefits.